Blockchain-based searchable symmetric encryption scheme. (January 2019) - Li, Huige; Tian, Haibo; Zhang, Fangguo; He, Jiejie
Abstract: The mechanism for traditional searchable symmetric encryption (SSE) is pay-then-use. This situation is not fair to user because the cloud server may return wrong results. Besides, the user needs to verify these results locally. In order to ensure fairness and reduce user's calculations, we combined blockchain with SSE, and proposed a fair SSE scheme based on blockchain. Our scheme can guarantee fairness for both parties. That is, if the user is not honest, he cannot get right results from the server, and at the same time the server cannot get any information related to the plaintexts during this search process. If the server is not honest, except for the service charge, it will be punished automatically. Moreover, the user in our scheme does not need to verify the results locally. The security and performance analyses showed our scheme was semantic secure and feasible.